2020
DOI: 10.1038/s41598-020-69254-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers for predicting the early onset of diabetic cardiomyopathy in a mouse model

Abstract: Type 2 diabetes (T2D) is characterized by metabolic derangements that cause a shift in substrate preference, inducing cardiac interstitial fibrosis. Interstitial fibrosis plays a key role in aggravating left ventricular diastolic dysfunction (LVDD), which has previously been associated with the asymptomatic onset of heart failure. The latter is responsible for 80% of deaths among diabetic patients and has been termed diabetic cardiomyopathy (DCM). Through in silico prediction and subsequent detection in a lept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Here, the exercise-induced decrease in fibrosis was accompanied by, even if not significant, clear lower protein levels of LOX following MIT. In silico predictive methods support that LOX-like 2, a LOX isoform known to play an important role in ECM cross-linking, can be used as an early biomarker for diabetic cardiomyopathy [ 98 ]. Contrary to our findings, 26 weeks of voluntary treadmill running by hypertensive rats induced increased gene and protein expression of LOX in the heart accompanied by diastolic dysfunction [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the exercise-induced decrease in fibrosis was accompanied by, even if not significant, clear lower protein levels of LOX following MIT. In silico predictive methods support that LOX-like 2, a LOX isoform known to play an important role in ECM cross-linking, can be used as an early biomarker for diabetic cardiomyopathy [ 98 ]. Contrary to our findings, 26 weeks of voluntary treadmill running by hypertensive rats induced increased gene and protein expression of LOX in the heart accompanied by diastolic dysfunction [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the remarkable changes of collagen matrix proteins in EtOH-treated hiPSC-CMs, these proteins could be potential biomarkers for alcoholic cardiomyopathy diagnosis. Indeed, growing evidence demonstrated that COL1A1 could serve as a biomarker candidate in a variety of cardiac diseases, such as diabetic cardiomyopathy and heart failure [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach and exploiting meta-analysis of transcriptomic datasets, differential expression levels of lysyl oxidase like 2 (LOXL2) and electron transfer flavoprotein beta subunit (ETFβ) in serum and heart tissue of 6-16-week-old db/db mice correlated closely with a reduced LV diastolic dysfunction, supporting the use of LOXL2 and ETFβ as early predictive biomarkers for diabetic CM. 126 Moreover, systematic multiorgan biobanking of porcine models of diabetes and obesity subjected to molecular profiling by transcriptomics, proteomics and metabolomics has been proposed to better understand tissue specific pathogenic mechanisms and organ crosstalk with the prospect of revealing novel molecular targets. 127 In the field of imaging technologies, the development of machine learning algorithms aims to provide more accurate biomarkers.…”
Section: Biomarkersmentioning
confidence: 99%